(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the means of expressing conditionality in modern Russian. It examines grammatical, lexical-semantic, and syntactic methods of expressing conditional relations, including conjunctive constructions and adverbial forms, and clarifies the role of structural models in complex sentences.